Widiyanti, Leny PERAN KUALITAS HUBUNGAN INTERPERSONAL GURU DAN PERKEMBANGAN KEPRIBADIAN SISWA MADRASAH IBTIDAIYAH : PERAN KUALITAS HUBUNGAN INTERPERSONAL GURU DAN PERKEMBANGAN KEPRIBADIAN SISWA MADRASAH IBTIDAIYAH - Widiyanti, Leny; Lilik Sriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the role of the quality of interpersonal relationships between teachers and students in shaping student personality at Madrasah Ibtidaiyah. The method used is a literature review, examining various relevant scientific sources on interpersonal communication, student personality, and Islamic educational values. The results of the study show that quality interpersonal relationships, characterized by effective communication, empathy, exemplary behavior, and teacher affection, have a significant influence on student personality development. Teachers play an important role not only as educators but also as spiritual guides and moral role models who instill Islamic values in every interaction. Through warm and attentive relationships, students feel valued, emotionally secure, and motivated to behave positively. Good interpersonal relationships foster students who are confident, disciplined, honest, independent, responsible, empathetic, and noble. Thus, the interpersonal relationship between teachers and students becomes the main foundation in realizing madrasah education that is character-building, religious, and oriented towards the formation of perfect human beings.